1989
DOI: 10.1017/s0950268800030004
|View full text |Cite
|
Sign up to set email alerts
|

Natural or vaccine-induced antibody as a predictor of immunity in the face of natural challenge with influenza viruses

Abstract: SUMMARYA study of influenza in residential schools provided the opportunity to assess the significance of antibody as a predictor of immunity. Five hundred and fifty-six pupils from 8 schools were included in the investigations, and the outcome for these children in 27 naturally occurring outbreaks of influenza was analysed. The outbreaks comprised 5 caused by strains of influenza A H3N2, 10 caused by strains of influenza A HIN1, and 12 caused by strains of influenza B. On 8 occasions a second outbreak of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 13 publications
0
43
0
Order By: Relevance
“…This approach, widely used and validated among GP based IVE studies, assumes that, by recruiting patients presenting with the same syndrome, we are likely to minimise selection biases [16][17][18]. In our study, A(H3N2) cases were of similar age as controls but tended to have less chronic diseases (non-significant differences).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This approach, widely used and validated among GP based IVE studies, assumes that, by recruiting patients presenting with the same syndrome, we are likely to minimise selection biases [16][17][18]. In our study, A(H3N2) cases were of similar age as controls but tended to have less chronic diseases (non-significant differences).…”
Section: Discussionmentioning
confidence: 97%
“…15,16 Recent past natural infections may play a booster role on the immunological response to seasonal vaccination. 17,18 Immune senescence 4 and a lower incidence of A(H1N1)pdm09 among elderly since the 2009 pandemic could partially explain the lower IVE against this subtype observed among patients. The higher IVE against A(H3N2) among elderly would require further investigation as it is in contradiction with the principles of immune senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between antibody levels (as measured by haemagglutination-inhibition [HI] titres) and protection against clinical disease is limited but the results of challenge studies with attenuated viruses and natural experiments during wild disease outbreaks suggest that HI antibody titres of 1:40 are associated with protection from influenza illness in up to 50% of subjects. 25,26 Influenza vaccine programmes Influenza vaccination programmes vary depending on the country -the UK operates one with both selective and universal components. The selective program provides protection for individuals at higher risk of infection -these include those aged 6 months to 64 years with chronic lung, heart, renal, liver and neurological conditions, the immunocompromised, people with diabetes, individuals with asplenia or hyposplenia and pregnant women.…”
Section: Disease Pathogenesis and Host Responsementioning
confidence: 99%
“…Furthermore, high antibody titres have been shown to prevent disease whereas lower titres modify disease severity. 1,26,27 In adults, neutralising antibodies to HA appear within about 7 days. Given that the majority will have been previously exposed to the same or similar epitopes through earlier infection, this is the response of primed individuals so the time to respond in na€ ıve children may be different and presumably longer.…”
Section: Influenza Vaccinesmentioning
confidence: 99%
“…Previous studies in school-children have shown that during influenza outbreaks a clinical diagnosis of influenza is confirmed in the laboratory in approximately 90% of cases (1). In the spring term of 1985 there was an outbreak of clinical influenza-like illness at Christ's Hospital, a boarding school in Sussex which then numbered some 675 boys aged 11-18 years.…”
Section: Introductionmentioning
confidence: 99%